2003
DOI: 10.1089/152308603768295195
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Monoxide Stimulates mrp2-Dependent Excretion of Bilirubin-IXα into Bile in the Perfused Rat Liver

Abstract: Although carbon monoxide (CO) has been reported to protect against hepatobiliary dysfunction, mechanisms for its actions remain unknown. This study aimed to examine actions of physiologically relevant concentrations of CO on biliary excretion. The effects of transportal administration of CO on bile output and constituents were examined in perfused rat livers. In livers of fed rats, CO regulated bile output biphasically in a dose-dependent manner; transportal administration of CO at 4 micro mol/L stimulated bil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…33 Conversely, CO overproduction by the HO-1 induction or exogenous administration of CO stimulates bile acid-independent choleresis concurrently with increased mrp2-dependent excretion of bilirubin-IX␣ and glutathione, while suppressing biliary excretion of bile salts, indicating the effects of the gas for stimulating fluid excretion into bile. 34 Of interest is that glibenclamide, an inhibitor of K ϩ channel that serves as a putative target for H 2 S, 26 acts on Na ϩ -K ϩ -2Cl Ϫ cotransporter in bile duct epithelium to stimulate biliary HCO 3 Ϫ excretion in normal and cholestatic livers. 35 We showed that inhibition of cystathionine ␥-lyase, another H 2 S-generating enzyme, stimulates basal and glibenclamide-induced fluid output of bile through stimulating HCO 3 Ϫ excretion without altering the baseline vascular resistance of the liver.…”
Section: Discussionmentioning
confidence: 99%
“…33 Conversely, CO overproduction by the HO-1 induction or exogenous administration of CO stimulates bile acid-independent choleresis concurrently with increased mrp2-dependent excretion of bilirubin-IX␣ and glutathione, while suppressing biliary excretion of bile salts, indicating the effects of the gas for stimulating fluid excretion into bile. 34 Of interest is that glibenclamide, an inhibitor of K ϩ channel that serves as a putative target for H 2 S, 26 acts on Na ϩ -K ϩ -2Cl Ϫ cotransporter in bile duct epithelium to stimulate biliary HCO 3 Ϫ excretion in normal and cholestatic livers. 35 We showed that inhibition of cystathionine ␥-lyase, another H 2 S-generating enzyme, stimulates basal and glibenclamide-induced fluid output of bile through stimulating HCO 3 Ϫ excretion without altering the baseline vascular resistance of the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, whether CO alone could alter the basal perfusion pressure was not tested in this study. In another recent study from the same research team, it was found that inclusion of CO (4 M) in the perfusate did not alter the vascular resistance of the isolated rat liver (Norimizu et al, 2003). At cellular level, CO activates sGC in hepatic stellate cells (Suematsu et al, 1995), which are sinusoidal pericytes controlling sinusoidal tone and blood flow distribution.…”
Section: F Carbon Monoxide and Livermentioning
confidence: 95%
“…CO regulates bile canalicular contractility in cultured rat hepatocytes (Shinoda et al, 1998). Norimizu et al (2003) reported that in perfused rat livers, transportal administration of CO at 4 M induced choleresis and increased baseline bile output by stimulating biliary excretion of bilirubin-IXa and glutathione. When the CO concentration increased beyond 10 M, bile output was no longer affected by CO.…”
Section: F Carbon Monoxide and Livermentioning
confidence: 99%
See 1 more Smart Citation
“…When perfused rat livers are administered concentrations of CO in the 4 to 6 μmol/L range, a choleresis is induced in which increased biliary excretion of bilirubin 1Xα, GSH, and bicarbonate are seen. These effects are dependent on the function of Mrp2 and tetraethylammonium (TEA) sensitive K + channels but are independent from cGMP-mediated secretion (414). This effect of CO may be a beneficial response to “stress” related events such as hypoxia and oxidative stress.…”
Section: Signal Transduction Pathways In the Regulation Of Bile Secrementioning
confidence: 99%